2002
DOI: 10.1038/sj.bjc.6600532
|View full text |Cite
|
Sign up to set email alerts
|

High level amplification of N-MYC is not associated with adverse histology or outcome in primary retinoblastoma tumours

Abstract: Twenty-five primary retinoblastoma tumours were analysed by real-time quantitative polymerase chain reaction to determine the genomic copy number of the N-MYC gene (2p24) relative to the copy number for REL, B2M, ALB, AF10 and MLL. Twenty-one of these tumours were shown by Comparative Genomic Hybridization to contain variable copy number increases of chromosomal material mapping to 2p. High level amplification (430-fold) of N-MYC was found in three tumours, none of which showed adverse histological features an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 25 publications
3
39
2
Order By: Relevance
“…The most prevalent karyotypic abnormality in retinoblastoma is gain of portions of the long arm of chromosome 1, seen in 21 of 27 tumors (Squire et al, 1985). At the higher resolution of comparative genomic hybridization (CGH), gain of a minimal region spanning 1q31 is the most common change seen in retinoblastoma in our study (Chen et al, 2001), and was seen cumulatively in 76/162 (47%) tumors across five published studies ( Figure 1a) (Mairal et al, 2000;Chen et al, 2001;Herzog et al, 2001;Lillington et al, 2002;van der Wal et al, 2003).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The most prevalent karyotypic abnormality in retinoblastoma is gain of portions of the long arm of chromosome 1, seen in 21 of 27 tumors (Squire et al, 1985). At the higher resolution of comparative genomic hybridization (CGH), gain of a minimal region spanning 1q31 is the most common change seen in retinoblastoma in our study (Chen et al, 2001), and was seen cumulatively in 76/162 (47%) tumors across five published studies ( Figure 1a) (Mairal et al, 2000;Chen et al, 2001;Herzog et al, 2001;Lillington et al, 2002;van der Wal et al, 2003).…”
Section: Introductionmentioning
confidence: 65%
“…Here, our initial QM-PCR analysis of 1q gain in retinoblastoma was consistent with the CGH literature ( Figure 1a) and showed good agreement with prior CGH and cytogenetic findings on individual retinoblastoma (Figure 2b), although the superior resolution of QM-PCR identified some gains not observed by CGH. QM-PCR with STSs more closely spaced around the initially identified hotspot defined a 3.06 Mbp minimal region of gain, centered around SHGC-154194, gained in 71% of retinoblastoma (Figure 2a), considerably more than the maximum (57%) seen in any CGH study (Lillington et al, 2002), indicating the high sensitivity of QM-PCR for genomic gain. The centromeric end of this 3.06 Mbp region includes the two most commonly gained markers (7/12 each) in the breast cancer cell lines studied (Figure 2c).…”
Section: Discussionmentioning
confidence: 99%
“…Amplification of a genomic region strongly suggests the presence of an oncogene, and MYCN has been well characterized as such by amplification in neuroblastoma (Schwab 2004) and less commonly in RB (Lee et al, 1984;Squire et al, 1986;Sakai et al, 1988;Choi et al, 1993;Doz et al, 1996;Mairal et al, 2000;Herzog et al, 2001;Lillington et al, 2002;Zielinski et al, 2005). Based on data from 87 tumors, we provide a robust estimate that MYCN amplification occurs in only 3% of primary RB.…”
Section: Genomic Copy Number Change Suggests Proliferative Statusmentioning
confidence: 95%
“…Previously, we used quantitative multiplex polymerase chain reaction (QM-PCR) and loss of heterozygosity analyses to narrow further three of these regions to ''hot spot'' sequence tagged sites (STS) at 1q32.1 (Corson et al, 2005), 6p22 (Chen et al, 2002), and 16q22 (Marchong et al, 2004). The 2p24 region is occasionally amplified in RB, and includes the MYCN oncogene, the assumed target of the amplification (Lee et al, 1984;Squire et al, 1986;Godbout et al, 1998;Lillington et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this genetic mutation, one possible target gene that may be an essential prognostic factor is N-myc , whose amplification is associated with poor prognosis in retinoblastoma [2] . However, N-myc amplification could not be detected in retinoblastoma tissues with PCR or Southern blot methods [3,4] . Recently, we also reported that N-myc amplification is rarely detected in retinoblastoma tissues by fluorescence in situ hybridiza-tion [5] , which was confirmed in a newly established retinoblastoma cell by comparative genomic hybridization [6] .…”
mentioning
confidence: 99%